VD_FINDINFO Décision / 2012 / 502 vom 26. Juni 2012 - VD Tribunal cantonal (2012)
DÉTENTION PRÉVENTIVE, PROPORTIONNALITÉ, RISQUE DE COLLUSION, SOUPÇON | 221 al. 1 let. b CPP (CH), 228 CPP (CH), 393 al. 1 let. c CPP (CH)